2017
DOI: 10.1021/acs.est.7b03525
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Airborne Measurements and Inventory Estimates of Methane Emissions in the Alberta Upstream Oil and Gas Sector

Abstract: Airborne measurements of methane emissions from oil and gas infrastructure were completed over two regions of Alberta, Canada. These top-down measurements were directly compared with region-specific bottom-up inventories that utilized current industry-reported flaring and venting volumes (reported data) and quantitative estimates of unreported venting and fugitive sources. For the 50 × 50 km measurement region near Red Deer, characterized by natural gas and light oil production, measured methane fluxes were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
127
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(142 citation statements)
references
References 43 publications
13
127
0
Order By: Relevance
“…The average production normalized leakage rate for satellite pads and well sites is 0.21%, while that for super pads is 0.03%. These proportional loss rates are lower than many recent studies of methane emissions in Canada [6,8]. Figure 2(b) shows the absolute methane leakage volumes as a function of production for the same set of sites in figure 2(a).…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…The average production normalized leakage rate for satellite pads and well sites is 0.21%, while that for super pads is 0.03%. These proportional loss rates are lower than many recent studies of methane emissions in Canada [6,8]. Figure 2(b) shows the absolute methane leakage volumes as a function of production for the same set of sites in figure 2(a).…”
Section: Resultsmentioning
confidence: 67%
“…This also indicates that it is possible for oil and gas operations to have leakage significantly lower than 1% even under a voluntary mitigation plan. Yet, evidence from many recent studies show methane emissions larger than reported or official inventory estimates [5,6]. It suggests that there might be significant differences in methane emissions across operators-a hypothesis with major implications for emissions policy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Red Deer), which are driven to conserve natural gas, and heavy oil developments (e.g. Lloydminister), which are associated with large emissions (Johnson et al 2017). However, conventional developments in the region have the lowest calculated emissions intensities across developments in North America, suggesting that differences in total emissions may be driven by a number of factors, such as differences in reservoir composition, regulation, age of the development and infrastructure, operator size and best practice, and field unitization.…”
Section: Infrastructure Typementioning
confidence: 99%
“…The September 1 st flight was used to calculate a regional mass-balance for the study region (Figure 1). Numerous previous studies have performed regional mass-balance experiments using analogous methodology Peischl et al, 2015;Heimburger et al, 2017;Johnson et al, 2017;Smith et al, 2017). Methane fluxes were calculated by multiplying background-subtracted CH 4 mole fraction (nmol mol -1 ), wind speed (m s -1 ) and dry air density (mol m -3 kg mol -1 ).…”
Section: Aircraft Measurementsmentioning
confidence: 99%